PERAN IBU DALAM PENYAMPAIAN PENDIDIKAN SEKSUAL PADA REMAJA PEREMPUAN DI KELURAHAN GANDEKAN, KECAMATAN JEBRES, KOTA SURAKARTA - Bima Eldo Yasafat; Bagus Haryono (Journal of Development and Social Change, 2020)
This research was conducted to describe the role of mothers in the delivery of teenage sex education in the Gandekan Village, Jebres District, Surakarta City. This type of research uses qualitative research methods with the case study method. Data collection uses participation collection, in-depth interviews, literature study, and documentation. The informants of this research are mothers who live in the Gandekan Village, Jebres District, Surakarta City. And having a teenage daughter. This study discusses the role that is carried out and which is carried out in the process of delivering the education section of their daughters. Using the AGIL theory (adaptation, goal achievement, integration, maintenance of latent patterns) put forward by Talcott Parsons, with four important basic elements that must be discussed in full and become a unity. The process is then processed. Data analysis techniques by collecting data, reducing data, presenting data and gathering conclusions.The results of this study indicate that there is a difference between the role of mothers who play a role and the role of mothers who are involved in the delivery of sexy education to girls in the Village Gandekan, Jebres District, Surakarta City. The ability of adaptation (Adaptation) by the mother regarding the development of the pattern of child relationships in the midst of technological development can be agreed to be adequate, the goal of achieving damage to the child's future. The way mothers provide sex education (integration) to children is done through advice, messages and rules or restrictions given to children. The mother's ability to support patterns (Latency) through implanting values is hardly adequate. This is evident from the fact that there are still many children who refute the advice given by the mother.